Target and effectiveness of service from a top player of tennis - Leontaridou, A.; Mavvidis, A.; Mantis, K. (Biology of Exercise, 2008)
The purpose of the current study was to go through the target and the effectiveness of the service in athletes of high standard. As an example, the No1 player of the world order, the Swiss Roger Federer, was used. 3 matches were carefully studied with the method of careful and repeated observation in a dvd, with the basic aim the detailed analysis of all of the well-aimed services, in connection with the point of their end in the court space which appoints their validity and the maximum number of the balls` exchange, at any time, until the point is judged. Federer`s first choice, concerning the direction of his service, was on the left of the opponent in the three matches of register (first match: 51,02%, second: 46,46%, third: 48,69%). He preferred to follow a maybe monotonous and unchangeable tactic in the execution of his service, because: a) the surface of the courts in which he faced his opponents was the same (quick-fast) and b) his three opponents were righthanded. However, when he chose the target «on the body of the opponent» the percentages of point`s success were better for him (statistically important, p .05). Generally, it was observed that after his well-aimed execution of the service, he gained the most points either with aces or very fast exchanging with his opponents with the maximum of 2 or 3 balls.